The Water Resources of an Island State (Jamaica): Issues Related: to Allocation, Accessibility, Management and Human Rights - Ahmed, Belal (Water Nepal, 2003)
Water is a fundamental survival need of mankind. In fact, denying people access to water is tantamount to denying them a basic human right. Still, about one billion people around the world do not have access to safe drinking water. In developing countries, especially in small island states, water assumes great importance in sustainable development. Although water is an economic resource, its availability is intrinsically related to the question of affordability by the public at large. This paper examines the issues related to water accessibility, supply, demand, management and governance in the Caribbean island of Jamaica. The development of new water supply schemes in Jamaica is being carried out by a private company, Carib Engineering Corporation Limited, while the distribution of water, maintenance works and minor water supply and sewage systems are the responsibility of the National Water Commission, a public sector organisation. Continued good governance is needed to make water more accessible to the public in Jamaica and in the Caribbean at large. Public and private sector efforts are required to educate the public regarding the misuse of water, the reuse of household wastewater and the recycling of industrial wastewater. A multi-partisan committee consisting of members of the public, community leaders and private and public sector representatives would ensure the free and fair distribution of water, transparency in dealings and the appropriate settlement of disputes at the national level. These initiatives are expected to contribute positively towards the equitable distribution and utilisation of water resources in the Caribbean island states.Water Nepal Vol.9-10, No.1-2, 2003, pp.391-390